What Lies Under the Chair! A Study in Ancient Egyptian Private Tomb Scenes, Part I: Animals - El-Kilany, Engy.
The depiction of daily life scenes in ancient Egyptian tombs is an expression of their way of life. It is a reflection of their ideas, concepts, messages, and lifestyle. The scenes of the chairs of the tomb owners, their wives, and their relatives reveal large numbers of items under those chairs. Those items can be classified into several groups, namely, animals, objects, and people. Each group consists of different elements. This paper, which is the first part of the study, concentrates on the animal group depicted under the chair. The aim of this paper is to categorize the animals under the chairs, identify the cause of their depiction in this place and discuss the possibility of dating the tomb through this depiction. This paper employs the descriptive-analytical methodology. Through studying over than one hundred tombs scenes from various periods, the findings revealed that animals under the chair are dogs, monkeys, cats, geese, ibexes, and gazelles. The possibility of dating the scenes from the Old and the New Kingdoms by identifying the animal under the chair is suggested as highly likely. Animal caretakers are only represented under the chair in the Old Kingdom while cats, geese, gazelles, and ibexes are only represented in the New Kingdom.